2016
DOI: 10.1155/2016/9132052
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Myo-Inositol and D-Chiro Inositol Treatment in Type 2 Diabetes

Abstract: Inositol has been used as a supplement in treating several pathologies such as PCOS, metabolic syndrome, and gestational diabetes. Both myo-inositol and its isomer d-chiro-inositol showed insulin mimetic effects in conditions of insulin resistance. Type 2 diabetes (T2DM) is a condition typically caused by insulin resistance. There is a lack of evidence of inositol use in T2DM. We evaluated the effectiveness and safety of myo-inositol and d-chiro-inositol treatment in T2DM. This was a pilot study involving a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 30 publications
(25 reference statements)
1
67
2
Order By: Relevance
“…In a pilot study involving 20 patients with type 2 diabetes mellitus, a combination of Myo 550 mg and DCI 13.8 mg added twice a day to glucose‐lowering drugs was associated with a significant reduction in blood glucose and HbA 1c levels after a 3‐month follow‐up . Sixty days of treatment with a fixed combination of Myo/DCI/Folic Acid (2000 mg/400 mg/400 μg, respectively) plus 10 mg of manganese was shown to significantly improve plasma lipids and blood glucose in a study carried out in 48 healthy pregnant women, enrolled between 13 and 24 weeks of gestation…”
Section: Clinical Effects Of Myo/dci Association Supplementationmentioning
confidence: 99%
“…In a pilot study involving 20 patients with type 2 diabetes mellitus, a combination of Myo 550 mg and DCI 13.8 mg added twice a day to glucose‐lowering drugs was associated with a significant reduction in blood glucose and HbA 1c levels after a 3‐month follow‐up . Sixty days of treatment with a fixed combination of Myo/DCI/Folic Acid (2000 mg/400 mg/400 μg, respectively) plus 10 mg of manganese was shown to significantly improve plasma lipids and blood glucose in a study carried out in 48 healthy pregnant women, enrolled between 13 and 24 weeks of gestation…”
Section: Clinical Effects Of Myo/dci Association Supplementationmentioning
confidence: 99%
“…In a study done by Pintadi B et al, in which they concluded that Myo-inositol and D-chiro-inositol are very effective in Control of insulin resistance. 19 Various studies have been conducted comparing Myoinositol with Metformin in obese women with infertility. In a study done by Awalekar Present study was directed towards comparing the use of Myo-inositol and D-chiro-inositol compared to Metformin alone where in, both the drugs led to statistically significant improvement in insulin resistance, over the period of 24 weeks, but the hormone profile (LH/FSH ratio and free testosterone) was well controlled in the Myo-inositol and D-chiro-inositol group.…”
Section: Discussionmentioning
confidence: 99%
“…DCI therefore acts as an insulin-sensitizing agent, and has shown promise as a treatment for diseases with glucose intolerance, such as polycystic ovarian syndrome (PCOS) and T2DM [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Myo-inositol (MYO-INS) and D-chiro-inositol (DCI) are stereoisomers of inositol which have been shown to exert insulinmimetic action and to lower postprandial glucose. In particular, DCI plays a key role in the insulin pathway, acting as insulin sensitizing through the enhancement of glucose peripheral tissue uptake and glycogen synthesis [7][8][9][10][11]. Thanks to these effects, they have been used for the treatment of insulin resistance states as polycystic ovary syndrome (PCOS), T2DM or GDM [12,13].…”
Section: Introductionmentioning
confidence: 99%